Resource-Guided Configuration Space Reduction for Deep Learning Models - Gao, Yanjie; Zhu, Yonghao; Zhang, Hongyu; Lin, Haoxiang; Yang, Mao (ICSE 2021, 2021)
Deep learning models, like traditional software systems, provide a large number of configuration options. A deep learning model can be configured with different hyperparameters and neural architectures. Recently, AutoML (Automated Machine Learning) has been widely adopted to automate model training by systematically exploring diverse configurations. However, current AutoML approaches do not take into consideration the computational constraints imposed by various resources such as available memory, computing power of devices, or execution time. The training with non-conforming configurations could lead to many failed AutoML trial jobs or inappropriate models, which cause significant resource waste and severely slow down development productivity. In this paper, we propose DnnSAT, a resource-guided AutoML approach for deep learning models to help existing AutoML tools efficiently reduce the configuration space ahead of time. DnnSAT can speed up the search process and achieve equal or even better model learning performance because it excludes trial jobs not satisfying the constraints and saves resources for more trials. We formulate the resource-guided configuration space reduction as a constraint satisfaction problem. DnnSAT includes a unified analytic cost model to construct common constraints with respect to the model weight size, number of floating-point operations, model inference time, and GPU memory consumption. It then utilizes an SMT solver to obtain the satisfiable configurations of hyperparameters and neural architectures. Our evaluation results demonstrate the effectiveness of DnnSAT in accelerating state-of-the-art AutoML methods (Hyperparameter Optimization and Neural Architecture Search) with an average speedup from 1.19X to 3.95X on public benchmarks. We believe that DnnSAT can make AutoML more practical in a real-world environment with constrained resources.
The 43rd International Conference on Software Engineering